Social work with people with learning difficulties - Williams, Paul; Evans, Michelle (Transforming social work practice, 2013)
Part of the Transforming Social Work Practice series, this title intends to support students on the social work degree. It seeks to confirm and strenghten social work values and principles so that the progress and successes achieved by 'Valuing People' can continue